Decentralized Creditor-Led Corporate Restructuring : Cross-Country Experience - Dado, Marinela E.; Klingebiel, Daniela (World Bank, Washington, DC, 2014)
Countries that have experienced banking crises have adopted one of two distinct approaches toward the resolution of non-performing assets-a centralized or a decentralized solution. A centralized approach entails setting up a government agency-an asset management company-with the full responsibility for acquiring, restructuring, and selling of the assets. A decentralized approach relies on banks and other creditors to manage and resolve non-performing assets. The authors study banking crises where governments adopted a decentralized, creditor-led workout strategy following systemic crises. They use a case study approach and analyze seven banking crises in which governments mainly relied on banks to resolve non-performing assets. The study suggests that out of the seven cases, only Chile, Norway, and Poland successfully restructured their corporate sectors with companies attaining viable financial structures. The analysis underscores that as in the case of a centralized strategy the prerequisites for a successful decentralized restructuring strategy are manifold. The successful countries significantly improved the banking system's capital position, enabling banks to write down loan losses; banks as well as corporations had adequate incentives to engage in corporate restructuring; and ownership links between banks and corporations were limited or severed during crises.